Factors influencing digital entrepreneurship intention among undergraduate business students in Jordan - Alkhalaileh, Mohammad Younis; Kovács, Sándor; Katonáné Kovács, Judit (Human Technology, 2023)
The digital revolution has completely changed the business structure, offering entrepreneurs and economies tremendous opportunities. The Jordanian government and universities recognized this potential and took steps to foster a digital entrepreneurship culture. However, despite these efforts, universities in Jordan have been relatively slow in supporting and integrating digital entrepreneurship culture. This study investigated the factors influencing digital entrepreneurship intention among 399 undergraduate students in Jordan. Partial Least Squares Modeling was used to analyze the data. The empirical findings indicated that digital entrepreneurship intention is directly influenced by attitude towards entrepreneurship and perceived behavioral control and indirectly by personality traits. However, subjective norms, digital literacy, and perceived university support did not significantly impact it. The findings of this study contribute to the growing body of knowledge on the role of digital literacy and socio-psychological factors in driving digital entrepreneurial intentions, offering valuable insight for future policy initiatives and educational strategies.